GURINDAM DUA BELAS KARYA RAJA ALI HAJI TERHADAP NILAI-NILAI PENDIDIKAN KARAKTER PERSPEKTIF PENDIDIKAN ISLAM - Kevin Aldino; Burhanuddin Ridlwan (JURNAL ILMIAH PENELITIAN MAHASISWA, 2024)
The aim of character education is to help students acquire the basic qualities they must have. Regarding character education, there is a Malay cultural heritage by a Malay poet and national figure, namely Raja Ali Haji. He also has a role in expressing values ​​in character and moral education. His work which discusses these values ​​is Gurindam Dua Belas. Considering the context of the situation that can be stated is what the values ​​of character education are in Gurindam Dua Belas by Raja Ali Haji, and what is perspective of Islamic education towards the values ​​of character education in Gurindam Dua Belas by Raja Ali Haji. Looking at this problem, two queries are possible to pose: what are the values ​​of character education contained in Gurindam Dua Belas by Raja Ali Haji, and what is perspective of Islamic education. The purpose of this research is to explain and evaluate the principles of character education. Descriptive library research is used in this kind of research. Data collection through documentation and library methods. After that, logic techniques are used to test the data according to the study's findings, it was discovered that 1. The forms of character education values ​​in Raja Ali Haji Gurindam Dua Belas: religious values, honest values, love of the country, values ​​of national spirit, friendship, love of peace, tolerance and responsibility. 2. The perspective of Islamic education on character education contained in Gurindam Dua Belas by Raja Ali Haji covers several scopes, including: a. Religious values: faith, devotion, and self-purification. b. Personal values: true values, fair values, non-arrogant values, generous values, frugal values, and patient values. c. Family values: The value of respecting parents, maintaining family life, and providing moral education. d. Social values: the value of gentleness, the value of trust, the value of respecting others, and the value of respecting teachers.